Endoplasmic reticulum-targeted phototherapy using one-step synthesized trace metal-doped carbon-dominated nanoparticles: Laser-triggered nucleolar delivery and increased tumor accumulation. (1st April 2019) - Bao, Yan-Wen; Hua, Xian-Wu; Li, Yan-Hong; Jia, Hao-Ran; Wu, Fu-Gen
Graphical abstract: Abstract: Lysosomal entrapment and liver accumulation are the two main obstacles faced by many anticancer drugs for achieving satisfactory therapeutic outcomes. Here, we develop a facile one-step hydrothermal synthetic route to prepare trace metal (M)-, N-, and O-doped carbon-dominated nanoparticles (termed as MNOCNPs, M = Ni, Pd, or Cu, metal content: <0.1 mol%) with exceptional photothermal properties (e.g., the ultrahigh extinction coefficient of 32.7 L g −1 cm −1 ), which can simultaneously realize preferable endoplasmic reticulum (ER) targeting and specific tumor enrichment without noticeable liver accumulation after poly(ethylene glycol) (PEG) conjugation. More interestingly, the PEG-modified MNOCNPs with nanoscale lengths exhibit considerable nucleolar delivery and increased tumor accumulation upon laser irradiation. After fluorescence labeling, these PEG-modified MNOCNPs are suitable for fluorescence/photoacoustic/thermal triple-modal imaging-guided photothermal cancer treatment. Additionally, the ultralow metal content ensures the exceptional biosafety of the nanoagents. The present work provides a novel, facile, and general synthetic method of carbon-dominated nanoparticles with superior photothermal properties for highly efficient tumor ablation, and the large-organelle (ER and nucleus)-targeted cancer therapeutic strategy may represent an alternative solution for optimizing the anticancer efficacy of nanomaterials. Statement of Significance: Limited wire-like nanomaterials have been used for biomedical applications due to their lack of intrinsic photothermal properties, poor cellular uptake and tumor accumulation, and potential biotoxicity arising from their micrometer lengths and/or massive heavy metal doping. Besides, the clinical applications of many nanoagents are hindered by their tendency to accumulate in liver, which may cause severe liver toxicity. Herein, we develop for the first time a one-step hydrothermal method to prepare wire-like trace metal-, N-, and O-doped carbon-dominated nanoparticles with excellent photothermal properties, massive cellular uptake, preferable ER localization, selective tumor targeting with negligible liver deposition, laser irradiation-enhanced nucleolar delivery and tumor accumulation, and multimodal imaging-guided cancer therapy. This work opens a new window for simultaneously overcoming lysosomal entrapment and liver accumulation in cancer therapy.